Development of AquaHeal 3.0: A Conceptual pH-Responsive Bioactive Hydrogel Dressing for Early Detection of Diabetic Foot Ulcers (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Diabetes mellitus is a major global health concern, and one of its most serious complications is the development of diabetic foot ulcers (DFUs), which often exhibit delayed healing, prolonged inflammation, high susceptibility to infection, and an increased risk of lower-limb amputation. Conventional wound dressings primarily provide physical protection but may not maintain an optimal wound environment or offer a simple method for monitoring changes in the wound. These challenges highlight the need for innovative, sustainable, and multifunctional wound dressing systems. The present work proposes AquaHeal 3.0, a conceptual multifunctional hydrogel dressing designed for academic research and future development. The dressing combines natural biodegradable polymers with bioactive ingredients and a visual pH indicator to create a sustainable wound-care platform. The proposed formulation consists of chitosan and sodium alginate as the hydrogel matrix, medical-grade honey, Aloe vera extract, and curcumin as natural bioactive components, Bromothymol Blue (BTB) as a visual pH indicator, a calcium-based cross-linking system for structural stability, a polyurethane (PU) protective film, and a medical adhesive border. The hydrogel matrix is conceptually designed to maintain a moist wound environment while absorbing wound exudate and supporting the controlled distribution of incorporated bioactive ingredients. Bromothymol Blue is intended to provide a simple visual indication of pH changes within the wound environment, which may assist in monitoring wound conditions. It is important to note that the pH indicator is not intended to diagnose infection, but rather to indicate changes in wound pH that may warrant further clinical assessment. The proposed development workflow includes conceptual stages of raw material selection, polymer preparation, hydrogel matrix formation, incorporation of bioactive ingredients, pH indicator incorporation, hydrogel cross-linking, casting, stabilization, protective film lamination, sterilization, packaging, and physicochemical characterization. The formulation is intended to undergo laboratory evaluation through parameters such as appearance, thickness, swelling behavior, moisture retention, water vapor transmission rate, mechanical strength, pH responsiveness, stability, and antimicrobial assessment in future experimental studies. AquaHeal 3.0 emphasizes the use of biodegradable biomaterials and naturally derived components, aligning with sustainable healthcare approaches and the principles of environmentally responsible biomaterial development. If future laboratory investigations demonstrate satisfactory safety, stability, and performance, the proposed concept may have potential applications in diabetic foot ulcer management and other chronic wound-care settings. However, the current work represents a conceptual academic formulation and does not constitute a clinically validated medical product. Further formulation optimization, biocompatibility studies, preclinical investigations, regulatory evaluation, and clinical trials would be required before any medical application. Overall, AquaHeal 3.0 provides a scientifically grounded conceptual framework for integrating biodegradable hydrogel technology, natural bioactive ingredients, and visual pH monitoring into a single multifunctional wound dressing platform for future research and innovation.
Keywords: Diabetic Foot Ulcer; Hydrogel Dressing; Chitosan; Sodium Alginate; Medical-Grade Honey